Development of supramolecular metal-organic type systems and nanotechnology applications - Araque, Juan Sebastian Aguirre (2019)
Polypyridine ruthenium complexes have attracted attention due to their remarkable photoelectronic properties and being employed as electron injection compounds in DSSCs, photo catalysts in water splitting among others. The first two chapters of this thesis present a comprehensive study of two novel ruthenium polypyridine and pyridine based complexes for DSSCs and for the study of an outer sphere intervalence electron transfer respectively. Porphyrins are organic structures commonly found in nature. Their outstanding chemical versatility, structural and electronic properties have made these compounds object of continuous research. Among these properties are enzymatic catalysis, transport and photoelectron generation. For these reasons the last two chapters of this thesis tried to focus in the development of supramolecular porphyrin arrangements capable of exploit and generate a synergistic effect of metallated cobalt porphyrins and polypyridine ruthenium complexes with opposite electronic properties -depending upon their - accepting or donating nature- and their interaction with GO as nanocomposites for effective tetraelectronic dioxygen reduction and isoniazid oxidation. These catalytic studies showed promising results as possible sensors for dioxygen and isoniazid when compared with reported methodologies.